Diferentes métodos de fixação da córnea no transplante lamelar anterior alógeno em coelhos - Marconato, Francieli (2011)
Domestic animals are often affected by corneal diseases and corneal repair main objective is to maintain ocular integrity and transparency of the cornea, avoiding the decrease in visual acuity. This study aimed to assess the viability of corneal allograft transplantation under different fixation methods such as polyglycolic acid, octyl-cyanoacrylate adhesive and fibrin glue. Therefore, 15 rabbits divided into three groups: group 1 - suture (G1 - 5 animals), group 2 - octyl-cyanoacrylate (G2 - 5 animals) and group 3 - fibrin adhesive (G3 - 5 animals) were used. In these animals a lamellar keratectomy of 5mm in diameter and 0.45 mm deep. The corneas were exchanged between the animals and for fixing, was held in the right eye several simple eight points, or cyanoacrylate adhesive or fibrin glue according to the group were used. Postoperatively, ophthalmic evaluations were performed daily and weekly with the aid of surgical microscope in addition to histopathology. Clinically significant differences for the variables blepharospasm, epiphora, corneal edema, conjunctival injection, pigmentation of the implant, the implant permanence, neovascularization and presence of hipopio. At the histopathology, in group 1 ocurred hyperplasia of the corneal epithelium, vessels and moderate inflammation. In group 2 hyperplasia of the corneal epithelium, neovascularization, pigmentation and moderate inflammatory reaction were observed. In group 3 slight hyperplasia of the corneal epithelium, absence of neovascularization and inflammation was found. It was concluded that fresh allogeneic transplantation can be used in lamellar keratoplasty without occurrence of rejection and that fibrin glue used for fixing the transplant showed better results in clinical and pathological corneas of rabbits.